Formes de corrosion littorale, côte sud du Saint-Laurent - Dionne, Jean-Claude (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1967)
Corrosion features were observed on the South Shore of the Maritime St. Lawrence Estuary, in conglomerate, limestone, sandstone, shale and cristalline boulders, and are here described for the first time.An attempt to classify these minor features characteristic of rocky shores is made and an extensive bibliography is given.An effort should be made to get more information on the geographical distribution of coastal corrosion forms on non calcareous rocks in cold regions.